Language Learning Analysis Used By Teachers In Teaching Learners In Islamic Boarding School (Study Of Qualitative) - Huriyah, Huriyah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The study aims to analyze learning process and language used by teachers in teaching learners in Islamic Boarding School. Qualitative method was used to understand learning process and language used by the teachers. The respondents in this research were teachers who care for learners that selected by purposive sampling based on the goal of research. While the techniques of collecting data consist of observation, interview and document study through Focus Group Discussion (FGD). The research findings show that learners in Buntet Islamic Boarding School learn about yellow book and its translation. The goal of learning the yellow book in order to the learners be able to read and understand about the content of Al-Qur’an and Al-Hadist. Bandingan method is used in teaching learners. This method is similar to reading method. In learning process, teachers open learning with opening salam, read poems and praises followed by learners together with best voice. Then teachers explain material with reading yellow book in Arabic, and translate it in Indonesian and Cirebonese language. While in the evaluation process, teachers evaluate learners in the end of semester